Influence of long-term application of composted or stockpiled feedlot manure with straw or wood chips on soil cation exchange capacity. Issue 1 (2nd January 2016) - Miller, Jim; Beasley, Bruce; Drury, Craig; Larney, Frank; Hao, Xiying
ABSTRACT: The influence of annual applications of composted (CM) or stockpiled (SM) beef feedlot manure with straw (ST) or wood-chip (WD) bedding on cation exchange capacity (CEC) of a clay loam soil in southern Alberta was examined after 1, 8, and 15 years. The hypotheses in our study were that soil CEC should be greater for amended than unamended soils; manure type and bedding should have no effect on soil CEC; and soil CEC should increase with greater manure application rate. After fifteen applications, the CEC was significantly greater for amended than unamended soils. Manure type had no significant ( P > 0.05) effect on soil CEC after fifteen applications, and the mean soil CEC was 5% greater for WD than ST. Mean CEC was significantly greater by 7 to 12% for the 77 than the 13 and the 39 Mg ha −1 rates after fifteen applications. The soil CEC was increased by 0.061 cmolc kg −1 for a unit increase in application rate (Mg dry wt. ha −1 yr −1 ), and 96% of the variation in CEC for amended soils could be explained by application rate. Overall, bedding, rate, or adjusting both bedding type and manure rate (but not manure type), may be possible practices for feedlot producers to manage soil CEC.